Postcoital Vaginal Rupture in a Young Woman with No Prior Pelvic Surgery. (16th March 2012) - Austin, Jennifer M.; Cooksey, Christie M.; Minikel, Laura L.; Zaritsky, Eve F.
ABSTRACT: Introduction. Reports of postcoital vaginal rupture in the literature are limited to cases involving women who are postmenopausal, have recently undergone pelvic surgery, or have suffered genitourinary trauma. Aim. We report a case of postcoital vaginal rupture in a 23‐year‐old woman with no prior surgical history who complained of acute onset, severe vaginal pain after consensual intercourse. Results. Examination under anesthesia revealed a 6‐cm laceration of the posterior fornix, which extended into the abdominal cavity. The laceration was repaired using a combined vaginal and laparoscopic approach. Conclusions. Coitus‐induced vaginal rupture in a reproductive aged woman with no prior pelvic surgery or other risk factors is a rare clinical presentation. Prior reports of rupture in premenopausal women have recommended repair via laparotomy. This case documents successful transvaginal and laparoscopic repair, and reviews the etiological mechanisms for coitus‐induced injury.Austin JM, Cooksey CM, Minikel LL, and Zaritsky EF. Postcoital vaginal rupture in a young woman with no prior pelvic surgery. J Sex Med 2013;10:2121–2124.